Feminism as seen in juana, the secondary character of john steinbeckâ€™s the pearl - Binawan, Heribertus ((JELE) Journal Of English Language and Education, 2019)
This study is intended to find out feminism in Juana, the secondary character of Steinbeckâ€™s â€œThe Pearlâ€. There are two problems that became the basis questions: (1) how is Juana characterized? (2) how is feminism revealed in Juana? To obtain the answers to the two questions above, a library study was carried out. It is done by studying the information and sources which were picked from referential books and studies of Steinbeckâ€™s work. Sociocultural approach is applied to analyze the story, since the problems have close relationship with people and their ideas of feminism. Social, cultural, and historical background is the factors that peopleâ€™s characteristics and build the ideas of feminism. Based on the result of analysis of the story, there are four points that can be concluded. First, the study on The Pearl has shown that Juana represents womanâ€™s struggles in the family. Second, there is a contrast between Kino and Juana. In contrast to the savage and brutal Kino, Juana retains the human qualities. Third, Juanaâ€™s feminism can be seen through her bravery to speak her idea about the pearl. Fourth, Juanaâ€™s feminism has made the story of The Pearl becomes full of conflicts.Â